Contemporary approach for uterine prolapse amputation in a goat - Gangwar, Chetna; Jajriya, Omprakash; Nandanwar, Kalyani; Mishra, Renuka; Agrawal, Jitendra; Singh, Diksha; Singh, Akash (Indian Journal of Veterinary Surgery, 2026)
-